2007
DOI: 10.1007/s00122-007-0587-0
|View full text |Cite
|
Sign up to set email alerts
|

The identification of candidate rice genes that confer resistance to the brown planthopper (Nilaparvata lugens) through representational difference analysis

Abstract: The development of rice varieties (Oryza sativa L.) that are resistant to the brown planthopper (BPH; Nilaparvata lugens Stål) is an important objective in current breeding programs. In this study, we generated 132 BC(5)F(5) near-isogenic rice lines (NILs) by five backcrosses of Samgangbyeo, a BPH resistant indica variety carrying the Bph1 locus, with Nagdongbyeo, a BPH susceptible japonica variety. To identify genes that confer BPH resistance, we employed representational difference analysis (RDA) to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…There is now considerable evidence to suggest that induced defenses are effective and have low fitness costs. Several studies have revealed that gene expression profiles in rice are reorganized in response to BPH feeding Yuan et al, 2005;Park et al, 2007;Wang et al, 2008). Such reorganization has been well documented in other plant-herbivore systems, supporting the hypothesis that inducible defenses contribute to rice resistance to the BPH.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…There is now considerable evidence to suggest that induced defenses are effective and have low fitness costs. Several studies have revealed that gene expression profiles in rice are reorganized in response to BPH feeding Yuan et al, 2005;Park et al, 2007;Wang et al, 2008). Such reorganization has been well documented in other plant-herbivore systems, supporting the hypothesis that inducible defenses contribute to rice resistance to the BPH.…”
Section: Discussionmentioning
confidence: 69%
“…Feeding by numerous BPHs on a single plant generally results in the susceptible plants yellowing, browning, and drying. In the last decade, the BPH has frequently caused widespread destruction of rice crops and heavy losses of yields (Shi et al, 2003;Park et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes involved with BPH resistance have been identiWed in rice plants using various molecular methods, such as cDNA array, suppression subtractive hybridization and representational diVerence analysis (RDA) (Ren et al 2004;Yuan et al 2004Yuan et al , 2005Zhang et al 2004;Wang et al 2005Wang et al , 2008bPark et al 2007). These genes belong to several functional groups, such as signaling pathways, oxidative stress/apoptosis, wound response and pathogen-related proteins.…”
Section: Introductionmentioning
confidence: 99%
“…These genes belong to several functional groups, such as signaling pathways, oxidative stress/apoptosis, wound response and pathogen-related proteins. We previously developed an eYcient RDA method to detect transcripts that are exclusively expressed in SNBC61, a BPH resistance near isogenic line (NIL), derived from backcrosses of Samgangbyeo carrying Bph1 with Nagdongbyeo, a BPH susceptible line (Park et al 2007). The isolated genes appear to be up-regulated in the resistant line and are closely located to known quantitative trait loci (QTLs) for BPH resistance.…”
Section: Introductionmentioning
confidence: 99%